Efficiency of Optical Non-Destructive Testing Method to Detect Surface Defects in Engineering Materials - Fattak, Leena Fahad (Nahrain University College of Engineering Journal, 2015)
Measuring of surface defects of engineering materials represent one of great importance engineering applications. The efficient use of detection of surface defect methods helps to avoid unreasonable high demands being made on surface quality.In this work, a simple laser system technique was used to detect the superficial defect. This is done through by the assessment of the laser light signals which are reflected from the work piece surface and detected by the photo diode detector. Theses signals are translated into final results which are corresponding to the type, geometry and dimensions of defects. An experimental arrangement using He–Ne laser light with measured maximum output power 4.5 mW and wavelength of 632.8 nm was incident on a sample, by using two convex lenses to collimate the light. The incident light was reflected and it was detected using the photo diode detector in the electronic analyzer circuit.Three different shapes of defects (conical, pyramid and scratch defects) were prepared on the two different materials (aluminum and iron). From the results, because of the total scattering of light, the defects have been identified through the detection and analysis of the intensity of the reflected rays, where the effect of pyramid defects was high.Optical methods were extremely useful for Non Destructive Testing (NDT) due to their ability to measure fast and contactless, to test larger areas or tiny spots in a short time, and to measure on complex shaped parts as well as plane surfaces.Finally, this paper describes the advancement of NDT towards a quantitative evaluation of the geometry and location of defects.